2019
DOI: 10.1177/1938965519877807
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Taste of High Status: Signaling Status at Restaurants

Abstract: Despite the prevalence of a common belief associating healthy eating with high status, the effect of such an intuitive association on consumer behavior remains unexamined. To fill this void, this research explores status signaling in a restaurant context. Two studies were conducted to examine the impact of consumers’ need for status on their preferences for healthy dining options. Results from Study 1 show that need for status has a positive effect on consumer preferences for a restaurant with a healthy (vs. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…It is not only important to provide healthy options on the menu but also necessary to strategically communicate the healthfulness status to prevent adversity. As such, this research expands the horizon of healthy dining literature through menu tactics (e.g., Shin & Mattila, 2020; Xu & Jeong, 2018).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is not only important to provide healthy options on the menu but also necessary to strategically communicate the healthfulness status to prevent adversity. As such, this research expands the horizon of healthy dining literature through menu tactics (e.g., Shin & Mattila, 2020; Xu & Jeong, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…Third, due to distinct dining environments and consumer needs, the messaging effect may differ by restaurant type. For example, fine dining restaurants often symbolize status consumption and recent research has revealed the status−signaling role of healthy choices (e.g., Shin & Mattila, 2020). As such, levels of psychological reactance toward an explicit message may be mitigated in a fine-dining context.…”
Section: Limitationsmentioning
confidence: 99%
“…Gentamicin, ciprofloxacin and vancomycin resistance were not detected. Poke bowls are becoming more popular, as it represents a combination of the health benefits of fish, salad and vegetables, complemented by a tasty sauce [35]. However, this dish contains raw fish, which may still represent microbiological risk for the consumer due to presence of pathogenic or potential pathogenic bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that a lower socioeconomic position is associated with more exposure to unhealthy food, which might lead to obesity and a shorter life expectancy [ 31 ]. People with a higher socioeconomic background do not only have access to a more healthy, balanced diet, but the consumer of such a diet is also perceived by other people as generally successful in life [ 32 ]. In other words, our diet can be showcased as a status symbol [ 33 , 34 ]—food as classism.…”
Section: Discussionmentioning
confidence: 99%